The faint-end of galaxy luminosity functions at the Epoch of Reionization. Issue Volume 12:Issue S333(2017) (8th May 2018) - Yue, B.; Castellano, M.; Ferrara, A.; Fontana, A.; Merlin, E.; Amorín, R.; Grazian, A.; Mármol-Queralto, E.; Michałowski, M. J.; Mortlock, A.; Paris, D.; Parsa, S.; et al.
Abstract: During the Epoch of Reionization (EoR), feedback effects reduce the efficiency of star formation process in small halos or even fully quench it. The galaxy luminosity function (LF) may then turn over at the faint-end. We analyze the number counts of z > 5 galaxies observed in the fields of four Frontier Fields (FFs) clusters and obtain constraints on the LF faint-end: for the turn-over magnitude at z ∼ 6, M UV T ≳-13.3; for the circular velocity threshold of quenching star formation process, v c * ≲ 47 km s −1 . We have not yet found significant evidence of the presence of feedback effects suppressing the star formation in small galaxies.